DETERMINATION CURIE POINT DEPTH BASED ON SPECTRUM ANALYSIS OF MAGNETIC ANOMALIES TO ESTIMATE THERMAL BASEMENT DEPTH - ANDRIANI (NIM : 20214005), DINI
Estimation of thermal basement depth is very important for identifying potential geothermal areas. In this study, specific approach has been applied by determine Curie Point Depth which utilizes demagnetization magnetic mineral of the crusts. Curie Point Depth is the depth of magnetic minerals in the crust which has been change from the ferromagnetic to paramagnetic as a result of increasing temperature. The bottom of the magnetized crust is interpreted as Curie point depth. Curie point depth of geothermal area was obtained from radially average power spectrum of magnetic anomalies data using spectrum analysis method with transform spatial domain to frequency domain. Curie point depth at survey area X have a depth vicinity 4000-4300 meter. Shallow Curie point depth at east survey area is 4087,2 meter and deep Curie point depth is 4370,1 at west survey area. Inversion has been applied using Levenberg-Marquardt technique as comparative information. The results illustrate that the inversion zones with high susceptibility contrast associated with the depth of the Curie point and zones with low susceptibility contrast associated with the shallow depth of the Curie point. Shallow Curie point depth appropriate with hot spring of near surface then that area is associated with heat source of near surface. An appropriate Curie point depth with geology setting can estimate potential geothermal resources.